1987
DOI: 10.1159/000195274
|View full text |Cite
|
Sign up to set email alerts
|

Ambroxol for the Prevention of Chronic Bronchitis Exacerbations: Long-Term Multicenter Trial

Abstract: In a 6-month, double-blind multicenter trial conducted over the winter, the effects of daily administration of ambroxol retard (75 mg) were compared with those of placebo in preventing exacerbations and improving symptoms and clinical signs in chronic bronchitis patients. The trial was completed by 110 patients in the ambroxol group and by 104 in the placebo group. Initially, there were no significant differences between the groups. By the end of the 2nd month of treatment, 67.2% of the ambroxol group had had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(20 citation statements)
references
References 4 publications
5
14
0
1
Order By: Relevance
“…While many of the clinical studies demonstrating the efficacy and tolerability of ambroxol have been generated prior to the introduction of Good Clinical Practice, a recent review has identified 92 clinical studies of acceptable quality [4]. Randomized, placebo-controlled short-term (up to 2 weeks of treatment) studies showed efficacy against endpoints such as ease of expectoration, phlegm loosening, sputum volume and sputum viscosity [1113]. Moreover, more recent studies have demonstrated the efficacy of ambroxol lozenges in the treatment of sore throat [14].…”
Section: Introductionmentioning
confidence: 99%
“…While many of the clinical studies demonstrating the efficacy and tolerability of ambroxol have been generated prior to the introduction of Good Clinical Practice, a recent review has identified 92 clinical studies of acceptable quality [4]. Randomized, placebo-controlled short-term (up to 2 weeks of treatment) studies showed efficacy against endpoints such as ease of expectoration, phlegm loosening, sputum volume and sputum viscosity [1113]. Moreover, more recent studies have demonstrated the efficacy of ambroxol lozenges in the treatment of sore throat [14].…”
Section: Introductionmentioning
confidence: 99%
“…BABOLINI [28] ALLEGRA [43] BORGIA [29] BOMAN [30] JACKSON [31] GRILLAGE [32] MCGAVIN [33] CREMONINI [35] CASTIGLIONI [36] OLIVIERI [37] RASMUSSEN [39] GRASSI [27] GRASSI [41] HANSEN [42] PELA [45] MEISTER [34] MEISTER [46] MALERBA [47] MORETTI [48] NOWAK [44] Total (95% CI) There is accumulating evidence that oxidative stress may play an important role in the pathogenesis of COPD. This is supported by enhanced exhalation of hydrogen peroxide [13], nitric oxide [16], ethane [17], carbon monoxide [16] and isoprostane [12,15], increased concentrations of 4-hydroxyl-2-nonenal in the lungs [19] or by increased urinary excretion of isoprostane [18].…”
Section: Presumptive Mechanisms Of Actionmentioning
confidence: 99%
“…The risk of infection can be reduced by clearing the bronchial tree [1]. Ambroxol is thought to be useful for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Ambroxol is thought to be useful for this purpose. Clinical studies of this drug have shown that it significantly improves the coughing and sputum production of patients with chronic bronchitis [1,2]. Mucoactive drugs such as ambroxol and carbocisteine have numerous pharmacological activities that inhibit bronchial secretion, including direct mucoregulatory effects on gland cells and mucociliary clearance, which are responsible for their clinical efficacy.…”
Section: Introductionmentioning
confidence: 99%